HYDROXYCARBAMINE: FROM AN OLD DRUG USED IN MALIGNANT HEMOPATHIES TO A CURRENT STANDARD IN SICKLE CELL DISEASE - Giovanna Cannas; Solene Poutrel; Xavier Thomas (Mediterranean Journal of Hematology and Infectious Diseases)
While hydroxycarbamine (hydroxyurea, HU) has less and less indications in malignant hemopathies, it represents the only widely used drug which modifies sickle cell disease pathogenesis. Clinical experience with HU for patients with sickle cell disease has been accumulated over the past 25 years in Western countries. The review of the literature provides increasing support of safety and efficacy in both children and adults for reducing acute vaso-occlusive events including pain episodes and acute chest syndrome. HU has become the standard-of-care for sickle cell anemia, but remains underused. Barriers to its use should be identified and overcome.